Publisher Correction: Atomic-scale engineering of ferroelectric-ferromagnetic interfaces of epitaxial perovskite films for functional properties. Issue 1 (December 2017) - Hausmann, Simon; Ye, Jingfan; Aoki, Toshihiro; Zheng, Jian-Guo; Stahn, Jochen; Bern, Francis; Chen, Binda; Autieri, Carmine; Sanyal, Biplab; Esquinazi, Pablo; Böni, Peter; Paul, Amitesh
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.